2013
DOI: 10.1186/1475-2840-12-54
|View full text |Cite
|
Sign up to set email alerts
|

Zinc protects against diabetes-induced pathogenic changes in the aorta: roles of metallothionein and nuclear factor (erythroid-derived 2)-like 2

Abstract: BackgroundCardiovascular diseases remain a leading cause of the mortality world-wide, which is related to several risks, including the life style change and the increased diabetes prevalence. The present study was to explore the preventive effect of zinc on the pathogenic changes in the aorta.MethodsA genetic type 1 diabetic OVE26 mouse model was used with/without zinc supplementation for 3 months. To determine gender difference either for pathogenic changes in the aorta of diabetic mice or for zinc protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 59 publications
(72 reference statements)
4
53
0
1
Order By: Relevance
“…It has been widely reported that MT offers antioxidative protection from various conditions, including diabetes in our own laboratory (9,10,24,37) and in others' (39,47). We found that diabetes decreased MT expression in the heart along with pathological cardiac damage.…”
Section: Discussionmentioning
confidence: 48%
“…It has been widely reported that MT offers antioxidative protection from various conditions, including diabetes in our own laboratory (9,10,24,37) and in others' (39,47). We found that diabetes decreased MT expression in the heart along with pathological cardiac damage.…”
Section: Discussionmentioning
confidence: 48%
“…Interestingly, in a similar study, zinc alone completely blocked inflammation and tissue remodeling associated with T1D in the aorta. Zinc strongly upregulated Nrf2 expression and ARE target NQO1 [79]. In neural tissues, glucoraphanin, a sulforaphane precursor, upregulated Nrf2, and reduced ROS in an induced murine model of Parkinson’s disease, reducing the severity of symptoms [80].…”
Section: Nutrient Gene Interactionsmentioning
confidence: 99%
“…Overall, decreased NO bioavailability with increased production of reactive nitrogen species as reported in animal and human studies of diabetes, supports a role for platelets in diabetes-induced endothelial and pulmonary injury (Figure 3). Studies in our laboratory have previously shown that genetically-induced antioxidant pathways, such as metallothionein (MT) or Nrf 2 (nuclear factor erythroid-related factor 2) overexpression, or pharmacological induction of these pathways by zinc administration (to induce MT) or sulforaphane (to induce Nrf2) alleviate DM-induced cardiac inflammation oxidative stress and fibrosis [2,84,85,86,87,88,89]. Ongoing similar studies are in progress in our laboratory to determine the role of this pathway in inducing platelet hyperreactivity and DM-induced lung fibrosis.…”
Section: Putative Signaling Mediating Diabetes-induced Microvasculmentioning
confidence: 99%